2004
DOI: 10.1038/sj.npp.1300428
|View full text |Cite
|
Sign up to set email alerts
|

Alpha2A-Adrenoceptors are Important Modulators of the Effects of D-Amphetamine on Startle Reactivity and Brain Monoamines

Abstract: Amphetamines are commonly used to treat attention-deficit hyperactivity disorder, but are also widely abused. They are employed in schizophrenia-related animal models as they disrupt the prepulse inhibition (PPI) of the acoustic startle response. The behavioral effects of amphetamines have mainly been attributed to changes in dopamine transmission, but they also involve increases in the synaptic concentrations of norepinephrine (NE). a 2 -Adrenoceptors (a 2 -ARs) regulate the excitability and transmitter relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 56 publications
5
31
0
Order By: Relevance
“…1M). To analyze whether the TASK-1 deletion affects the functions of noradrenergic neurons, we tested the sensitivity of TASK-1 knockout mice to dexmedetomidine, which produces strong sedative/hypnotic and hypothermic effects by inhibiting noradrenaline release through activation of presynaptic ␣ 2 -adrenergic receptors (Lä hdesmä ki et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1M). To analyze whether the TASK-1 deletion affects the functions of noradrenergic neurons, we tested the sensitivity of TASK-1 knockout mice to dexmedetomidine, which produces strong sedative/hypnotic and hypothermic effects by inhibiting noradrenaline release through activation of presynaptic ␣ 2 -adrenergic receptors (Lä hdesmä ki et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the reduced sensitivity to the sedative effects of dexmedetomidine in the knockouts suggests alterations in the noradrenergic system, which may underlie enhanced acoustic startle response. Indeed, it has been reported that dexmedetomidine attenuates acoustic startle responses by reducing firing of noradrenergic neurons (Lä hdesmä ki et al, 2004). However, it is also possible that the disruption of TASK-1 enhances neuronal excitability outside the noradrenergic system.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, the a-1 NE antagonist prazosin and the 5HT 2 antagonist ketanserin failed to reverse cocaine-induced PPI deficits (van der Elst et al, 2006), while the NE reuptake inhibitor desipramine, but not the 5HT reuptake inhibitor citalopram, normalized amphetamine-induced PPI disruptions (Pouzet et al, 2005). In mice, a2A-KO mice were more sensitive to amphetamine-induced PPI disruption (Lahdesmaki et al, 2004) and NET is potentially involved in cocaine-induced PPI disruptions (Yamashita et al, 2006). Future studies should include a DA uptake inhibitor with little affinity for other neurotransmitter pathways to help elucidate the mechanistic differences between amphetamine and cocaine in terms of effects on PPI.…”
Section: Discussionmentioning
confidence: 95%
“…A few studies using transgenic mice have shown that mice lacking the a2C receptor have disrupted PPI (Sallinen et al, 1998) while mice lacking the a1D receptor or the a2A receptor do not show the same magnitude of disruption in PPI after psychotomimetic drug administration as wild-type mice (Lahdesmaki et al, 2004;Mishima et al, 2004). It must be pointed out though, that a recent study examined the effects of the a2 antagonist yohimbine on PPI and found that while yohimbine disrupts PPI, this effect may in part be due to its actions at serotonin-1A receptors (Powell et al, 2005).…”
Section: Discussionmentioning
confidence: 99%